QUALITY OF LIFE IN THE ELDERLY (CIPEEX, 2024)
POPULATION AGING IS A GLOBAL PHENOMENON CHARACTERIZED BY AN INCREASE IN THE PROPORTION OF ELDERLY INDIVIDUALS IN SOCIETY, RESULTING FROM DECLINING BIRTH RATES AND INCREASED LIFE EXPECTANCY. UNDERSTANDING AND IMPROVING THE QUALITY OF LIFE (QOL) OF THE ELDERLY IS ESSENTIAL FOR BUILDING MORE INCLUSIVE AND SUSTAINABLE SOCIETIES. THE OBJECTIVE OF THIS STUDY IS TO ASSESS THE PERCEPTION OF THE ELDERLY REGARDING THEIR QUALITY OF LIFE. THE RESEARCH INSTRUMENT USED WAS THE WHOQOL-OLD QUESTIONNAIRE, WHICH PROVIDES INSIGHTS INTO THE PHYSICAL AND PSYCHOLOGICAL HEALTH, SOCIAL RELATIONSHIPS, AND THE ENVIRONMENT IN WHICH THE ELDERLY LIVE. THE QUESTIONNAIRE WAS ADMINISTERED THROUGH GOOGLE FORMS, ONLINE VIA A WHATSAPP LINK, TO 30 ELDERLY INDIVIDUALS OF BOTH SEXES RESIDING IN THE CITY OF URUANA, GOIS. REGARDING THE PHYSICAL ASPECT, THE RESEARCH RESULTS PRESENT A MIXED SCENARIO IN RELATION TO THE QOL OF THE PARTICIPANTS: THERE IS EVIDENCE THAT MOST ELDERLY INDIVIDUALS FEEL CAPABLE OF DOING WHAT THEY WOULD LIKE AND ARE SATISFIED WITH OPPORTUNITIES FOR NEW ACHIEVEMENTS, INDICATING AN OVERALL SENSE OF AUTONOMY AND WELL-BEING. HOWEVER, DISSATISFACTION WITH THE LEVEL OF ACTIVITY AND THE PRESENCE OF COMPLAINTS OF PAIN AND AGE-RELATED DISEASES POINT TO CHALLENGES AND MAY BE INDICATIVE OF A POTENTIAL DECLINE IN SOCIAL PARTICIPATION AND QOL, POTENTIALLY NEGATIVELY IMPACTING PHYSICAL AND EMOTIONAL WELL-BEING. THE RESULTS IN THE PSYCHOLOGICAL ASPECT, AS INDICATED BY THE MAJORITY OF RESPONDENTS, ARE ENCOURAGING AND SUGGEST A POSITIVE STATE OF EMOTIONAL WELL-BEING. THE FACT THAT THEY FEEL HAPPY WITH THEIR LIFE ACCOMPLISHMENTS AND ARE SATISFIED WITH HOW THEY SPEND THEIR TIME DEMONSTRATES A SENSE OF CONTENTMENT AND PERSONAL GRATIFICATION. THE POSITIVE RESULTS IN THE SOCIAL ASPECT, AS INDICATED BY THE FEELING OF COMPANIONSHIP AND OPPORTUNITIES FOR LOVE, UNDERSCORE THE IMPORTANCE OF INTERPERSONAL RELATIONSHIPS IN THE LIVES OF ELDERLY INDIVIDUALS AND HIGHLIGHT THAT MANY ARE EXPERIENCING HEALTHY AND SATISFYING SOCIAL RELATIONSHIPS, CONTRIBUTING TO QOL AND THE PROMOTION OF HEALTHY AND FULFILLING AGING. BASED ON THE ABOVE, IT CAN BE CONCLUDED THAT THE QOL OF THIS POPULATION IS INFLUENCED BY A COMBINATION OF COMPLEX FACTORS, BUT LARGELY POSITIVE. IT IS EMPHASIZED THAT THERE IS A NEED FOR POLICIES AND INTERVENTIONS THAT PROMOTE THE PHYSICAL AND EMOTIONAL HEALTH OF THE ELDERLY. WITH HOLISTIC AND PERSONALIZED APPROACHES, IT IS POSSIBLE TO CONTRIBUTE TO HEALTHIER AGING.
Keywords: Quality of Life; Elderly; Perception; WHOQOL-OLD